Composite construction of cold-formed steel (CFS) section with high strength bolted shear connector - Lawan, Mustapha Muhammad (2015)
Composite construction is well known to be effectively used in the construction of buildings and bridges using hot rolled steel (HRS) and headed studs connectors. The shear connectors provides the enhancement as established in current design codes. In this paper, the shear connection mechanism was proposed using high strength bolted shear connector to provide composite action between concrete and the steel section. The conventional headed stud shear connector was eliminated since Cold-formed steel (CFS) was used and welding was not practically possible due to thinness nature of the CFS section. Therefore, in this study investigation was carried out on the strength capacity, ductility and the ultimate flexural capacity of the proposed high strength bolted shear connector and the composite beam specimens respectively. Four push-out and two full-scale composite beam specimens were fabricated using high strength M16 bolted shear connector of Grade 8.8 connected to the top flanges of the CFS I-section and tested to failure using push-out and four-point bending tests respectively. The results show that ultimate load and ultimate moment capacities of the proposed system were significantly improved by using the proposed connectors. The experimental results were compared with theoretical results based on the provision of Eurocode 4, and good agreement between the results was observed. In conclusion, compared results proved that the ultimate moment capacity of the proposed composite beams can be estimated efficiently by using the constitutive laws as prescribed by Eurocodes and British standards.